A study on the design and space efficiency of general chemistry laboratories in the University of the Philippines - Chan, Liezl Anne Sophia; Mayo, Adelaida Villaraza (1990.)
(no abstract provided by the author)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Space (Architecture).; Architectural designs; University of the Philippines (Diliman).